2020
DOI: 10.1038/s41380-020-00955-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal unsnarling of brain’s acute neuroinflammatory transcriptional profiles reveals panendothelitis as the earliest event preceding microgliosis

Abstract: Sepsis-associated encephalopathy (SAE) is an acutely progressing brain dysfunction induced by systemic inflammation. The mechanism of initiation of neuroinflammation during SAE, which ultimately leads to delirium and cognitive dysfunction, remains elusive. We aimed to study the molecular events of SAE to capture its onset and progression into the central nervous system (CNS), and further identify the cellular players involved in mediating acute inflammatory signaling. Gene expression profiling on the cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 62 publications
(71 reference statements)
1
49
0
Order By: Relevance
“…The highest number of differentially expressed genes being in endothelial cells suggests that vascular cells could be the initial responders to viral transduction and expression of the transgene. This is supported by Kodali et al, who have shown that endothelial cells are the first to elicit a response to peripheral inflammatory stimulation by transcribing genes for proinflammatory mediators and cytokines (Kodali et al, 2020). With regards to p53 differentially expressed genes, Ghouzzi, et al have also shown that the genes Phdla3, Aen, and Cdkn1a were upregulated in cells infected with ZIKA virus, signifying genotoxic stress and apoptosis induction (Ghouzzi et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The highest number of differentially expressed genes being in endothelial cells suggests that vascular cells could be the initial responders to viral transduction and expression of the transgene. This is supported by Kodali et al, who have shown that endothelial cells are the first to elicit a response to peripheral inflammatory stimulation by transcribing genes for proinflammatory mediators and cytokines (Kodali et al, 2020). With regards to p53 differentially expressed genes, Ghouzzi, et al have also shown that the genes Phdla3, Aen, and Cdkn1a were upregulated in cells infected with ZIKA virus, signifying genotoxic stress and apoptosis induction (Ghouzzi et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Immediate early genes such as Ier2 (Kodali et al, 2020) were upregulated across pericytes, endothelial cells, inhibitory neurons, and OPCs at 3 DPI, while Fos, Ier2, Junb, and Arc were prominent in excitatory neurons at 25 DPI.…”
Section: Figure 5 Single-cell Gene Expression Profiling Finds Cell-type-specific Responses To Aav Transduction In Vascular Cells and Excimentioning
confidence: 97%
“…Several mechanisms are involved in SAE pathogenesis, such as disturbance of the blood–brain barrier (BBB), neuronal apoptosis, endothelial activation, hyperinflammation produced by inflammatory cytokines release, oxidative stress, neurotransmission disturbances by alteration in neurotransmitter level, altered brain signaling, altered microcirculation, and dysregulated metabolism [ 5 , 46 ]. Recently, Kodali et al demonstrated that cerebral endothelial cells (CECs) are the first activated cells during the earliest stages of acute neuroinflammation, defined as a spinal cord or brain inflammatory response, mediated by cytokine, chemokine, and oxidative stress production [ 47 , 48 ]. Kodali et al [ 47 ] suggested that CECs are the main source of proinflammatory mediators, which in turn can promote glial cell activation, such as microglial activation.…”
Section: Physiopathology Of Saementioning
confidence: 99%
“…Recently, Kodali et al demonstrated that cerebral endothelial cells (CECs) are the first activated cells during the earliest stages of acute neuroinflammation, defined as a spinal cord or brain inflammatory response, mediated by cytokine, chemokine, and oxidative stress production [ 47 , 48 ]. Kodali et al [ 47 ] suggested that CECs are the main source of proinflammatory mediators, which in turn can promote glial cell activation, such as microglial activation. Furthermore, Kodali et al [ 47 ] observed that SAE continued by activating apoptotic signaling in CECs, which is known that causes a BBB disruption, allowing the entrance of peripheral cytokines into the CNS and thus causing an exacerbate gliosis.…”
Section: Physiopathology Of Saementioning
confidence: 99%
See 1 more Smart Citation